The #shitholes Syllabus: Undoing His(Story) - Rodriguez, Clelia O. (Radical Teacher, 2018)
This text politicizes unlearning processes in #shitholes presented in the format of an unconventional syllabus. My proposed questions to readers in light of the Trumpism era are: How are they made? Who has created them? Do you know where they are located? If you looked at a map, can you point them out? What are they? When do they appear?